Supporting Young Learners During Remote Education: How Context and Gender Shape Adolescent Experiences - Maddaleno-Herrera, M (Elsevier Inc., 2024)
Purpose: The COVID-19 pandemic prompted a global closing of schools that raised questions on the implications for students. This study examines the impact of remote education, and subsequent social isolation, on adolescent well-being among urban poor young adolescents worldwide. Methods: Qualitative data were collected through focus group discussions with urban poor adolescents in 7 countries and 8 sites, for a total sample size of 249 adolescents. Discussion guides addressed attitudes toward remote education strategies and its perceived impact on health, relationships, and learning. Analysis used an inductive thematic coding approach, with comparison by site and gender. Results: Adolescents experienced opposite extremes of remote education, with those from lower-income sites feeling abandoned by educators and systems and those from higher-income sites feeling increased external pressure and loneliness. Both boys and girls reported declining mental health, although boys reported more access to support structures than girls. All students missed connections with peers and teachers. Discussion: Although all adolescents struggled with remote education, their challenges differed by context and gender. School systems should consider conducting a student needs assessment to ensure future remote education is accessible and beneficial to adolescents in each site. Families and teachers should take a gender-equal approach to assistance, ensuring adolescents have equal opportunities and agency to reach out for, and receive, educational and emotional support. © 2024